Hatching for 3D prints: Line-based halftoning for dual extrusion fused deposition modeling. (August 2018) - Kuipers, Tim; Elkhuizen, Willemijn; Verlinden, Jouke; Doubrovski, Eugeni
Highlights: A halftoning technique is proposed for dual extrusion FDM systems. It enables the full range of grayscale tones for any surface angle. Dimensional inaccuracy incurred is within 0.1 millimeter. Minimal influence on structural properties of 3D prints. Approx. 15% extra print time and 20% extra process planning time. Graphical abstract: Abstract: This work presents a halftoning technique to manufacture 3D objects with the appearance of continuous grayscale imagery for Fused Deposition Modeling (FDM) printers. While droplet-based dithering is a common halftoning technique, this is not applicable to FDM printing, since FDM builds up objects by extruding material in semi-continuous paths. The line-based halftoning principle called 'hatching' is applied to the line patterns naturally occurring in FDM prints, which are built up in a layer-by-layer fashion. The proposed halftoning technique is not limited by the challenges existing techniques face; existing FDM coloring techniques greatly influence the surface geometry and deteriorate with surface slopes deviating from vertical or greatly influence the basic parameters of the printing process and thereby the structural properties of the resulting product. Furthermore, the proposed technique has little effect on printing time. Experiments on a dual-nozzle FDM printer show promising results. Future work is required to calibrate the perceived tone.